Ankle-brachial index: more than a diagnostic test? - Caceres-Farfan, Ludwig (2021)
The ankle-brachial index (ABI) is the relationship between the systolic blood pressure taken at the ankle level and the brachial artery. A pathological ABI (<0.90 or >1.40) indicates the presence of peripheral artery disease (PAD). Many studies indicate the great utility of this test in the diagnosis of PAD due to its ease of use, reproducibility, low cost, and high cost-effectiveness. This evaluation can be directly correlated with cardiovascular morbidity and mortality; however, it has recently been confirmed that a low ABI can be a predictor of major cardiovascular events, as it is related to diabetes mellitus, chronic coronary disease, stroke, and more. The objective of this work was to review the current evidence on the importance of ABI in the diagnosis of PAD and its main role as a predictor of cardiovascular morbidity and mortality.